Lower female survival from an opportunistic infection reveals progesterone-driven sex bias in trained immunity - Alexander P. Earhart; Natalia G. Karasseva; Kathryn M. Storey; Benjamin Olthoff; Md Bodruzzaman Sarker; Kimberly G. Laffey; Margaret J. Lange; R. Scott Rector; Laura C. Schulz; Diana Gil; Claudia M. Neuhauser; Adam G. Schrum (Cell Reports, 2023)
Summary: Immune responses differ between females and males, although such sex-based variance is incompletely understood. Observing that bacteremia of the opportunistic pathogen Burkholderia gladioli caused many more deaths of female than male mice bearing genetic deficiencies in adaptive immunity, we determined that this was associated with sex bias in the innate immune memory response called trained immunity. Female attenuation of trained immunity varies with estrous cycle stage and correlates with serum progesterone, a hormone that decreases glycolytic capacity and recall cytokine secretion induced by antigen non-specific stimuli. Progesterone receptor antagonism rescues female trained immune responses and survival from controlled B. gladioli infection to magnitudes similar to those of males. These data demonstrate progesterone-dependent sex bias in trained immunity where attenuation of female responses is associated with survival outcomes from opportunistic infection.